2013
DOI: 10.1088/0964-1726/22/8/084015
|View full text |Cite
|
Sign up to set email alerts
|

Smart hexagonal truss systems exhibiting negative compressibility through constrained angle stretching

Abstract: Negative compressibility is the ability to expand in at least one dimension rather than shrinking upon the application of an externally applied hydrostatic pressure. It is shown that, contrary to current perception, negative linear compressibility may be obtained from re-entrant hexagonal truss systems of specific geometric features which deform through non-equal changes in the lengths of the cell walls when deforming through a constrained angle stretching rather than other modes of deformation (such as flexur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 22 publications
1
49
0
Order By: Relevance
“…1 it is observed that m ! À1/3, which is consistent with equations given by Grima et al [21] for regular hexagonal lattices with the angles between bars constrained. In this second case the structure's compliance is dominated by the axial springs.…”
Section: Results: 2d Latticessupporting
confidence: 91%
See 1 more Smart Citation
“…1 it is observed that m ! À1/3, which is consistent with equations given by Grima et al [21] for regular hexagonal lattices with the angles between bars constrained. In this second case the structure's compliance is dominated by the axial springs.…”
Section: Results: 2d Latticessupporting
confidence: 91%
“…In the limit as k s ! 1 the structure will become like the one discussed in reference [21]. The axial deformation dominated structures are stiffened by repulsive nearest neighbor interactions and softened by attractive nearest neighbor interactions, due to the equivalent linearized axial stiffness of magnetic interactions being positive for repulsion and negative for attraction.…”
Section: Results: 2d Latticesmentioning
confidence: 79%
“…Auxetic foams have some interesting mechanical properties including, synclastic curvature and improved resilience , indentation resistance , shear resistance , fracture toughness , energy dissipation and vibration damping . In certain density regions, auxetic foams and isotropic auxetic continua can also display negative bulk modulus and negative compliance .…”
Section: Introductionmentioning
confidence: 99%
“…Due to their counter-intuitive properties, auxetic materials have been investigated as smart materials for potential applications including cushion materials [9], stents [10,11], pressure vessels [12], sensors [13], morphing airfoils [14,15], smart folding structures [16], smart metamaterials [17], aeroengine fan blades [18], and vibration dampers [19], to name a few. Arising from their unique properties, the mechanical performance of auxetic solids has been investigated [20][21][22][23][24][25][26][27][28][29][30][31][32][33], including their elastic stabilities [34][35][36]. Additionally, investigations in the dynamic behavior of auxetic solids and structures have also been performed [37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%